Pengaruh Metode Permainan Kata Teka-Teki Silang dan Anagram terhadap Penguasaan Kosakata Siswa Kelas IV - Siska Nurma Yunitasari; Anang Santoso; Ari Sapto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Vocabulary mastery is crucial to be taught to elementary school students because it significantly affects the student’s language skills. This research was aimed to explain the influence of wordplay method such as crosswords and anagramss toward the vocabulary mastery of elementary school students. This study used a pretest posttest control group design with a sample of 36 students. The hypothesis test carried out using anacova test. The result show that there is a significant effect on the wordplay method include crosswords and anagrams to vovabulary mastery with the sig. value of 0,000 < 0,05.Abstrak: Penguasaan kosakata sangat penting untuk diajarkan kepada peserta didik di sekolah dasar karena hal tersebut sangat memengaruhi keterampilan berbahasa peserta didik. Tujuan penelitian ini adalah untuk menjelaskan pengaruh metode permainan kata teka-teki silang dan Anagram terhadap penguasaan kosakata siswa sekolah dasar. Penelitian ini menggunakan pretest-posttest control group design dengan sampel 36 peserta didik. Uji hipotesis dilakukan dengan uji Anacova. Hasil penelitian menunjukkan bahwa terdapat pengaruh signifikan metode permainan kata teka-teki silang dan Anagram terhadap penguasaan kosakata dengan nilai Sig. 0,000 < 0,05.